Factors affecting on compliance of childhood immunization in Ilam District of Nepal; A case-control study - Bina Sigdel; Yan Jin; Pushpa Dhakal; Tika Luitel; Pushpa Kumari Ghimire; Sharada P. Wasti (Elsevier, 2023)
Childhood immunization is one of the most important public health interventions to reduce child morbidity and mortality. Reaching all children with full immunization services is critical to meet Nepal's commitment to Sustainable Development Goals (SDGs). This study aimed to identify factors affecting compliance with childhood immunization in children aged 16 to 36 months in Nepal. A community-based unmatched case-control study was conducted with 250 (83 cases and 167 controls) respondents in the Ilam district of Nepal. Respondents were randomly selected using a multi-stage cluster sampling technique. Data were collected using a structured questionnaire and analysed using SPSS version 16 statistical software. Bivariate and multivariate logistic regression analyses were done to identify the factors influencing compliance with childhood immunization of the sampled respondents. More than two-thirds (66.8%) of the sampled children were fully immunized, and 19.3% of the children defaulted to the Measles-Rubella vaccines. Only 19.2% of the respondents had good knowledge about the type of vaccine, and more than half (59.2%) of the respondents had a positive attitude towards immunization. Multivariate logistic regression analysis revealed that lack of knowledge about vaccines (AOR = 49.4, 95% CI = 12.94 to 188.59), father's level of education (AOR = 2.1, 95% CI = 1.05 to 4.30), not getting immunization on the day of the appointment (AOR = 4.8, 95% CI = 2.30 to 9.89), lack of knowledge about immunization schedule (AOR = 2.4, 95% CI = 1.14 to 4.84), and negative attitude towards immunization (AOR = 2.1, 95% CI = 1.03 to 4.19) were independently impeded on compliance on the childhood immunization. Targeted intervention in health promotion activities at the household level should be promoted and integrated immunization services into the existing primary health care services.